Students Speak: Do College Exit Exams Unleash Motivation or Fuel Stress? - Mulisa, Feyisa; Kejela, Mekonnen (International Journal of African Higher Education, 2025)
College exit exams serve as indicators of students' academic achievement and career readiness. However, a significant concern is the stress these exams may impose on students. Some students may also question the usefulness of these exams, which can negatively affect their performance. The purpose of this article is to evaluate students' perceptions of the relevance, validity, motivation, the ability to promote self-awareness, and the stress associated with exit exams. To gather data, we administered questionnaires and conducted interviews with 113 students who had taken an exit exam at Ambo University. The findings indicate that students generally have moderately positive perceptions regarding the relevance and validity of the exit exams. Additionally, the exams were found to be highly motivating and effective tools for identifying individual strengths and weaknesses. While this positive perception is an opportunity to increase the effectiveness of the exam, the paradox is that it is stressful for female students. Therefore, it is essential to pay special attention to the experiences of female students. The implication is that by considering students' experiences, we can create a supportive and inclusive environment that promotes academic achievement and overall well-being.